ANALISA SEMANTIK PRODUK PADA DESAIN SIGER LAMPUNG PESISIR DALAM FOTO PRE-WEDDING NIKITA WILLY - Vania Aqmarani Sulaiman (Universitas Mercu Buana, 2021)
Traditional clothing is one of the traditional cultures which is still favored and used on various occasions. So in other words, traditional clothing today has the potential to be developed into a novelty following today's lifestyle. This renewal is none other than the result of the needs of today's human lifestyle regardless of whether or not the original meaning of traditional clothing has changed. Currently, there are a lot of design developments from traditional Lampung clothing, starting from the shape, size, to the material. These changes are caused by changes in lifestyle and current environmental conditions. It is not yet certain whether these changes still contain the same meaning and image as the original design of the traditional clothing itself, while the preservation of the original meaning of traditional clothing is very important for the preservation of the culture itself. When a design is changed or developed without considering the message from the maker, there is a possibility that the message of the design will shift.This research aims to review the meaning of the traditional wedding dress of the women of the Lampung Pesisir, namely Siger through a case study and literature study review. The research object chosen was Nikita Willy's pre-wedding photo due to the newness of the photo publication, so that it was considered that the Siger used was also a new product. The results of the research will be in the form of a collection of design review data from Siger Lampung Pesisir used in Nikita Willy's pre-wedding photo. The results of this research will be useful for the development of similar product designs so that they can meet and answer the need for fashion products with local cultural content that are per the needs of today's lifestyle but still uphold the original values of the culture. The method used in this research is descriptive qualitative, namely the collection of data in the form of literature review related to Siger women of the Lampung tribe both from its history and the meaning contained in the product. The researcher then used product semantic theory as a means of translating the meaning and characteristics of the design of the research object.